Effect of Inorganic N Top Dressing and Trichoderma harzianum Seed-Inoculation on Crop Yield and the Shaping of Root Microbial Communities of Wheat Plants Cultivated Under High Basal N Fertilization - Illescas, María; Rubio, M. Belén; Hernández-Ruiz, Víctor; Morán-Diez, María E.; Martínez de Alba, A. Emilio; Nicolás, Carlos; Monte, Enrique; Hermosa, Rosa (Frontiers in Plant Science, 2020)
Wheat crop production needs nitrogen (N) for ensuring yield and quality. High doses of inorganic N fertilizer are applied to soil before sowing (basal dressing), with additional doses supplied along the cultivation (top dressing). Here, a long-term wheat field trial (12 plots), including four conditions (control, N top dressing, Trichoderma harzianum T34 seed-inoculation, and top dressing plus T34) in triplicate, was performed to assess, under high basal N fertilization, the influence of these treatments on crop yield and root microbial community shaping. Crop yield was not affected by top dressing and T. harzinum T34, but top dressing significantly increased grain protein and gluten contents. Twenty-seven-week old wheat plants were collected at 12 days after top dressing application and sampled as bulk soil, rhizosphere and root endosphere compartments in order to analyze their bacterial and fungal assemblies by 16S rDNA and ITS2 high-throughput sequencing, respectively. Significant differences for bacterial and fungal richness and diversity were detected among the three compartments with a microbial decline from bulk soil to root endosphere. The most abundant wheat root phyla were Proteobacteria and Actinobacteria for bacteria, and Ascomycota and Basidiomycota for fungi. An enrichment of genera commonly associated with soils subjected to chemical N fertilization was observed: Kaistobacter, Mortierella and Solicoccozyma in bulk soil, Olpidum in rhizosphere, and Janthinobacterium and Pedobacter in root endosphere. Taxa whose abundance significantly differed among conditions within each compartment were identified. Results show that: i) single or strain T34-combined application of N top dressing affected to a greater extent the bulk soil bacterial levels than the use of T34 alone; ii) when N top dressing and T34 were applied in combination, the N fertilizer played a more decisive role in the bacterial microbiome than T34; iii) many genera of plant beneficial bacteria, negatively affected by N top dressing, were increased by the application of T34 alone; iv) bulk soil and rhizosphere fungal microbiomes were affected by any of the three treatments assayed; and v) all treatments reduced Claroideglomus in bulk soil but the single application of T34 raised the rhizosphere levels of this mycorrhizal fungus.